2017
DOI: 10.3389/fpls.2017.00787
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Salicylic Acid Treatment in Rehmannia glutinosa Hairy Roots Using RNA-seq Technique for Identification of Genes Involved in Acteoside Biosynthesis

Abstract: Rehmannia glutinosa is a common bulk medicinal material that has been widely used in China due to its active ingredients. Acteoside, one of the ingredients, has antioxidant, antinephritic, anti-inflammatory, hepatoprotective, immunomodulatory, and neuroprotective effects, is usually selected as a quality-control component for R. glutinosa herb in the Chinese Pharmacopeia. The acteoside biosynthesis pathway in R. glutinosa has not yet been clearly established. Herein, we describe the establishment of a genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 72 publications
0
38
1
8
Order By: Relevance
“…The biosynthetic pathway of acteoside in Olea europaea has been characterized [22]. In R. glutinosa , two biosynthetic pathways are involved in the biosynthesis of the processor of phenylethanoid glycosides: the phenylalanine-derived pathway and the tyrosine-derived pathway [18] (Figure 7A). In the phenylalanine-derived pathway, phenylalanine is metabolized to caffeoyl-CoA through phenylalanine ammonia-lyase (PAL), cinnamate-4-hydroxylase (C4H), coumarate-3-hydroxylase (C3H), and 4-coumarate-CoA ligase (4CL).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthetic pathway of acteoside in Olea europaea has been characterized [22]. In R. glutinosa , two biosynthetic pathways are involved in the biosynthesis of the processor of phenylethanoid glycosides: the phenylalanine-derived pathway and the tyrosine-derived pathway [18] (Figure 7A). In the phenylalanine-derived pathway, phenylalanine is metabolized to caffeoyl-CoA through phenylalanine ammonia-lyase (PAL), cinnamate-4-hydroxylase (C4H), coumarate-3-hydroxylase (C3H), and 4-coumarate-CoA ligase (4CL).…”
Section: Resultsmentioning
confidence: 99%
“…Catalpol and acteoside are usually selected as the two quality-control components in the R. glutinosa herb and have been included in the Chinese Pharmacopoeia since the 2015 edition. Considering limited genomic information coupled with genome complexity (polyploidy), several reports about the catalpol and acteoside biosynthesis pathway have been seen in some studies [16,17,18], but the molecular regulation mechanism needs to be deeply studied.…”
Section: Introductionmentioning
confidence: 99%
“…Given that studies focussing solely on isolated contributary factors often fail to yield meaningful insights into the important elements of biological processes, we designed the present study with a view towards characterising an integrated environment comprising pine hosts, RISs, and PWNs. Simple treatment using RISs is limited to the detection of general genes (termed pathogenesis-related genes) under SAR conditions [ 67 , 68 ], whereas PWN infection in pine trees predominantly reflects the pathogenic mechanisms within dying cells [ 69 ]. Consequently, the integrated design of the present study enabled us to assess the sequential stages of RIS treatment and infection, as well as the activation of related genes under conditions of SAR induction, thereby facilitating subsequent analyses of the essential mechanisms underlying the protection against and inhibition of PWN.…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been spent to understand the cascades of reactions that result in the formation and accumulation of secondary metabolites in plant cells in response to SA. In this sense, it has been shown that signaling molecules lead to genetic expression and biochemical changes in a specific metabolic pathway [93,94]. Additionally, a whole-genome approaches such as metabolic and transcriptomic profiling in the roots of Arabidopsis [95], in the seeds of Triticum estivum L. [96], in Rehmannia glutinosa hairy roots [94] and in Scutellaria baicalensis [97], have been used to determine the genes specifically regulated in response to SA treatment.…”
Section: Salicylic Acid Phospholipid Signaling and Secondary Metabolmentioning
confidence: 99%